Monatomic iron anchored covalent triazine skeleton and green synthesis method and application thereof
By synthesizing single-atom iron-anchored covalent triazine skeleton Fe-CTFs using gradient heating method under air atmosphere, the problems of complexity and environmental pollution of traditional CTFs synthesis methods are solved, gentle, simple and low-cost synthesis is achieved, and the stability and redox performance of the catalyst are improved.
Patent Information
- Application Number
- CN202510248824.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-06-03
AI Technical Summary
The synthesis method of traditional covalent triazine frameworks (CTFs) is complex and requires high temperature and super acid catalysis, which leads to high energy consumption and environmental pollution, and has low crystallinity, which hinders the further development of materials.
A green synthesis method of single-atom iron-anchored covalent triazine framework was adopted. By mixing 1,4-terephthaldehyde, terephthalamidine hydrochloride and alkaline catalyst under an air atmosphere, the gradient temperature was heated up at 60°C-120°C for condensation reaction, the iron source was added and the reaction temperature was maintained to continue the reaction, and the single-atom iron-anchored covalent triazine framework Fe-CTFs were obtained.
It realizes gentle, simple, low-cost and environmentally friendly synthesis of CTFs, enhances the stability of the catalyst, improves the redox performance, and has broad application prospects.
Smart Images

Figure CN120082052A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of organic polymer material synthesis, and relates to a single-atom iron-anchored covalent triazine framework, a green synthesis method thereof, and an application thereof. Background Art
[0002] Among various organic materials, covalent triazine frameworks (CTFs for short) are a class of organic polymer materials rich in nitrogen, having a conjugated structure, functional triazine groups, and a relatively high porosity. Their structural formula is shown as follows:
[0003]
[0004] Based on their structural characteristics and combined with the high thermal and chemical stability of organic polymer materials, CTFs have broad application prospects in the fields of gas adsorption and separation, catalysis, energy storage, etc.; however, the synthesis methods of CTFs are often relatively complex. For example, the ionothermal method requires high temperatures of 400 - 600 °C, which not only increases energy consumption but also limits its application in large-scale industrial production; another example is the superacid catalysis method, which requires the use of superacids (such as trifluoromethanesulfonic acid) to catalyze the triazine cyclization reaction of aromatic nitrile monomers. The use of superacids may cause environmental pollution, and the post-treatment of the reaction is complex and requires additional neutralization steps.
[0005] In recent years, in the field of organic chemical synthesis, most reported CTFs have low crystallinity or even are completely amorphous, which has hindered the further development of this material to a certain extent. Improvement strategies for this type of material can be divided into heterogeneous structure construction, crystal form transformation, metal / non-metal element doping, etc., but there are still many challenges in its development. Single-atom catalysts, especially transition metal-nitrogen-carbon materials, show excellent catalytic activity for the oxygen reduction reaction. Single-atom iron catalysts have stronger covalent bonds with non-metal atoms on the surface of the carrier, have better stability than the corresponding nano-catalysts, and iron single-atom materials have characteristics such as environmental compatibility, high specific surface area, and functionality, and have incomparable natural advantages in degrading aqueous solution pollutants. Therefore, it is very urgent to develop and design a general strategy for synthesizing covalent triazine frameworks anchored with single-atom iron, and the synthesis process needs to be mild, efficient, and environmentally friendly. Summary of the Invention
[0006] The purpose of the present invention is to solve the deficiencies of the above traditional technologies and provide a general strategy for a green synthesis method of a single-atom iron-anchored covalent triazine framework. CTFs have a π-conjugation effect and rich N coordination sites, and can form metal-N xCoordination structures are used to introduce metal elements. When metal-doped covalent triazine frameworks (M-CTFs) are photoexcited, there is an acceptor-donor-acceptor electron transfer channel among the triazine rings, benzene rings, and metal ions in the structure, which can effectively improve the migration rate and separation efficiency of photogenerated carriers. This strategy has the advantages of mild reaction conditions, simple operation, low cost, environmental friendliness, high yield, etc. In addition, the introduction of transition metals such as iron and cobalt also facilitates the realization of photoinduced self-Fenton reactions by the catalyst, showing great application potential in the fields of environment and water treatment.
[0007] The object of the present invention is achieved by the following technical measures:
[0008] In the first aspect, the present invention provides a green synthesis method for single-atom iron-anchored covalent triazine frameworks, specifically:
[0009] Under an air atmosphere, 1,4-phthalaldehyde, p-phenylenediamidine hydrochloride, and a basic catalyst are mixed and dissolved in a solvent, and a condensation reaction is carried out by gradient heating at 60 °C - 120 °C; when the reaction temperature reaches 120 °C, an iron source is added and the reaction temperature is maintained to continue the reaction to obtain a product, which is washed and dried to obtain the single-atom iron-anchored covalent triazine framework Fe-CTFs, wherein the iron element accounts for 0.5% - 4% of the mass of the single-atom iron-anchored covalent triazine framework Fe-CTFs; the iron source is a soluble salt of divalent or trivalent iron, and its anion is selected from at least one of chloride ions, nitrate ions, and sulfate ions.
[0010] Further, the molar ratio of 1,4-phthalaldehyde to p-phenylenediamidine hydrochloride is 1:(1.5 - 2.5), preferably 1:2.
[0011] Further, the basic catalyst is cesium carbonate.
[0012] Further, the iron source is ferrous sulfate (FeSO 4 ·7H 2 O).
[0013] Further, the solvent is a mixed solvent of dimethyl sulfoxide and water.
[0014] Further, the gradient heating is specifically: heating and reacting at 60 °C for 12 - 14 h, then raising the temperature to 80 °C and heating and reacting for 12 - 14 h, then raising the temperature to 100 °C and heating and reacting for 12 - 14 h, and finally raising the temperature to 120 °C.
[0015] Further, the reaction time after adding the iron source is 72 - 76 h, preferably 72 h.
[0016] Further, the iron element accounts for 2% of the mass of the single-atom iron-anchored covalent triazine framework Fe-CTFs.
[0017] In a second aspect, the present invention provides a single-atom iron-anchored covalent triazine framework, which is prepared by the above method.
[0018] In a third aspect, the present invention provides the application of the above single-atom iron-anchored covalent triazine framework in photocatalytic pollutant degradation.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0020] 1. The Fe-CTFs of the present invention are synthesized by a one-pot method. The synthesis steps are simple, the reaction conditions are mild, and the operation is convenient. During the reaction process, the method of gradient heating is adopted. The rich N coordination sites can coordinate with metal iron ions under heating conditions to form a more stable Fe-N x coordination structure, thereby enhancing the stability of the catalyst.
[0021] 2. The preparation method of the present invention has a wide application range, is environmentally friendly, and has broad application prospects.
[0022] 3. The single-atom anchored organic polymer material of the present invention realizes interlayer bonding through Fe-N bonds, and has relatively excellent activity and stability. Based on the introduction of single-atom iron, the Fe-CTFs are endowed with more reactive sites and more excellent redox performance than the original CTFs. Description of the Drawings
[0023] Figure 1 It is a comparison chart of the activities of samples synthesized by different synthesis methods.
[0024] Figure 2 It is the X-ray diffraction pattern (XRD) of the original CTFs and Fe-CTFs.
[0025] Figure 3 It is a comparison chart of the degradation activities of the original CTFs and CTFs loaded with single-atom iron in different proportions. Detailed Embodiments
[0026] The present invention will be described more comprehensively and clearly below with reference to the drawings and embodiments, but the present invention is not limited to the scope of the described embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts fall within the scope of protection of the present invention.
[0027] As described above, the present invention provides a preparation method for a single-atom iron-anchored covalent triazine framework, which includes the following steps:
[0028] In an air atmosphere, 1,4-phthalaldehyde and p-phenylenediamidine hydrochloride with a molar ratio of 1:(1.5 - 2.5) are mixed and a basic catalyst is added, then a mixed solvent of dimethyl sulfoxide and water is added. The mixture is heated and reacted at 60 °C for 12 - 14 h, then the temperature is raised to 80 °C and heated and reacted for 12 - 14 h, subsequently the temperature is raised to 100 °C and heated and reacted for 12 - 14 h, and finally the temperature is raised to 120 °C, and an iron source (7.5 - 60 mg) with a mass fraction of 0.5% - 4% is added. The reaction temperature is maintained and the reaction continues for 72 - 76 h to obtain a product. After washing successively with dilute hydrochloric acid solution, water, acetone, and tetrahydrofuran (THF), it is dried to obtain the single-atom iron-anchored covalent triazine framework Fe-CTFs;
[0029] Among them, the basic catalyst is cesium carbonate; the iron source can be selected according to actual needs, such as soluble salts of divalent or trivalent iron, and its anion is selected from at least one of chloride ion, nitrate ion, and sulfate ion; preferably ferrous sulfate, which is easily soluble in water, is convenient for uniform doping, and has low cost and is easy to obtain; the meaning of the mass fraction is that the iron element in the iron source accounts for 0.5% - 4% of the mass of Fe-CTFs.
[0030] The following further describes the present invention; unless otherwise specified, the raw materials used in the examples are all commercially available or prepared by conventional methods.
[0031] Example 1: Preparation of single-atom iron-anchored covalent triazine framework organic polymer material (Fe-CTFs)
[0032] 1,4-Phthalaldehyde (67.2 mg, 0.5 mmol), p-phenylenediamidine hydrochloride (235.2 mg, 1.0 mmol) and cesium carbonate (716.8 mg, 2.2 mmol) are added to a 25 mL round-bottom flask, and then 5.0 mL of dimethyl sulfoxide (DMSO) and 0.2 mL of water are added and mixed well. Keeping the stirring condition, the mixture is heated and reacted at 60 °C, 80 °C, and 100 °C for 12 h respectively, then the temperature is raised to 120 °C and FeSO 4 ·7H 2 O with a mass fraction of 2% is added, and the reaction continues with heating and stirring for 3 days to obtain a brown-yellow solid. Among them, the stirring speed is 420 revolutions per minute.
[0033] Preferably, the obtained precipitate is washed with dilute hydrochloric acid solution (3 × 10 mL) to remove salts and residual cesium carbonate, then washed with water (3 × 10 mL), acetone (3 × 10 mL) and THF (3 × 10 mL), and placed in an oven at 60 °C for drying for 12 h. The sample is named Fe-CTFs.
[0034] The structural formula of Fe-CTFs is shown as follows:
[0035]
[0036] Example 2: Synthesis of Fe-CTFs with different ratios
[0037] Add 1,4-phthalaldehyde (67.2 mg, 0.5 mmol), p-phenylenediamidine hydrochloride (235.2 mg, 1.0 mmol) and cesium carbonate (716.8 mg, 2.2 mmol) into a 25 mL round-bottom flask. Then add 5.0 mL of dimethyl sulfoxide (DMSO) and 0.2 mL of water respectively and mix well. Keeping the stirring condition, heat the mixture at 60 °C, 80 °C and 100 °C for 12 h respectively, then raise the temperature to 120 °C and add FeSO 4 ·7H 2 O with mass fractions of 0.5%, 1%, 2% and 4% respectively, and continue to heat and stir for 3 days to obtain a brownish-yellow solid. Among them, the stirring speed is 420 revolutions per minute.
[0038] Preferably, wash the obtained precipitate with dilute hydrochloric acid solution (3×10 mL) to remove salts and residual cesium carbonate, then wash with water (3×10 mL), acetone (3×10 mL) and THF (3×10 mL), and then dry in an oven at 60 °C for 12 h. The prepared samples are 0.5-Fe-CTFs, 1-Fe-CTFs, 2-Fe-CTFs (i.e., the product of Example 1) and 4-Fe-CTFs.
[0039] Example 3:
[0040] Add 1,4-phthalaldehyde (67.2 mg, 0.5 mmol), p-phenylenediamidine hydrochloride (235.2 mg, 1.0 mmol) and cesium carbonate (716.8 mg, 2.2 mmol) into a 25 mL round-bottom flask. Then add 5.0 mL of dimethyl sulfoxide (DMSO) and 0.2 mL of water respectively and mix well. Keeping the stirring condition, heat the mixture at 60 °C, 80 °C and 100 °C for 14 h respectively, then raise the temperature to 120 °C and add FeCl 3 ·6H 2 O with a mass fraction of 2%, and continue to heat and stir for 76 h to obtain a brownish-yellow solid. Among them, the stirring speed is 420 revolutions per minute.
[0041] Preferably, wash the obtained precipitate with dilute hydrochloric acid solution (3×10 mL) to remove salts and residual cesium carbonate, then wash with water (3×10 mL), acetone (3×10 mL) and THF (3×10 mL), and dry in an oven at 60 °C for 12 h to obtain a single-atom iron-anchored covalent triazine framework organic polymer material Fe-CTFs.
[0042] Comparative Example 1: Preparation of covalent triazine framework organic polymer material CTFs
[0043] 1,4 - terephthalaldehyde (67.2 mg, 0.5 mmol), p - phenylenediamidine hydrochloride (235.2 mg, 1.0 mmol) and cesium carbonate (716.8 mg, 2.2 mmol) were added to a 25 mL round - bottom flask. Then, 5.0 mL of dimethyl sulfoxide (DMSO) and 0.2 mL of water were added respectively and mixed well. Under stirring conditions, the mixture was heated at 60 °C, 80 °C, and 100 °C in an oil bath for 12 h respectively, and then heated and stirred at 120 °C in an oil bath for three days (the above rotation speed was 420 revolutions per minute), obtaining a yellow solid.
[0044] Preferably, the obtained precipitate was washed with dilute hydrochloric acid solution (3×10 mL) to remove salts and residual cesium carbonate, and then washed with water (3×10 mL), acetone (3×10 mL) and THF (3×10 mL), and then dried in an oven at 60 °C for 12 h, obtaining a yellow powder, and the sample was named CTFs.
[0045] Comparative Example 2: Synthesis of iron - loaded CTFs by physical stirring method
[0046] Take 20 mg of the CTFs synthesized in Comparative Example 1 and 4 mg of FeSO 4 ·7H 2 O into a 10 mL round - bottom flask. Subsequently, 10 mL of ethanol was added. After mixing well, it was stirred at 40 °C in an oil bath at a rotation speed of 400 revolutions per minute for 6 h. The obtained solution was centrifuged and filtered, and placed in an oven at 60 °C for 6 h. The sample was named PS - Fe - CTFs.
[0047] Comparative Example 3: Synthesis of iron - loaded CTFs by calcination method
[0048] Take 20 mg of the CTFs synthesized in step 1) and 4 mg of FeSO 4 ·7H 2 O and grind them evenly in a mortar. Subsequently, put them into a porcelain boat, wrap the surface of the porcelain boat with tin foil, and place it in a tubular furnace to calcine for 1 h under argon conditions at a heating rate of 2 °C / min. The sample synthesized based on the calcination method was named CM - Fe - CTFs.
[0049] Test Example
[0050] As a method for laboratory verification and inspection of the characteristics of the above - mentioned polymer photocatalytic material, after the device (photocatalytic device, generally including a light source: xenon lamp (300 W xenon lamp, PLS - SXE300, China); reactor: quartz tube; stirring system: magnetic stirrer; temperature control system: cooling system, etc.) was stable, under the irradiation of simulated visible light by the xenon lamp, a photocatalytic pollutant (the pollutant was doxycycline) degradation reaction was carried out, and the degradation activity of the reactant was recorded every 15 minutes.
[0051] Figure 1 Degradation activity comparison chart of Fe-CTFs synthesized under different synthesis conditions. As Figure 1 shown, the Fe-CTFs synthesized by the one-pot method have the best activity for degrading pollutants.
[0052] Figure 2 X-ray diffraction patterns of CTFs and Fe-CTFs. After the introduction of Fe, stable bonding with N is formed, promoting more stable connection of the lamellae. The characteristic peaks of the 100 plane and the 001 plane can be accurately corresponding for both the original CTFs material and the composite CTFs material after anchoring single-atom Fe, proving the stability of the materials synthesized by this synthesis method.
[0053] Figure 3 For further exploration of the degradation activity of composite catalysts with different proportions of anchored single-atom Fe. As shown in the figure, compared with other Fe-doping ratios, 2-Fe-CTFs is the optimal sample for degradation.
[0054] The above embodiments are not limitations on the present invention. The present invention is not limited to the above embodiments. As long as it meets the requirements of the present invention, it belongs to the protection scope of the present invention. In addition, it should be understood that after reading the above description content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims of this application.
Claims
1. A green synthesis method of a single-atom iron-anchored covalent triazine skeleton, characterized in that: Specifically: In an air atmosphere, 1,4-terephthalaldehyde, terephthalamidine hydrochloride and an alkaline catalyst are mixed and dissolved in a solvent, and the temperature is gradually increased at 60°C-120°C for condensation reaction; when the reaction temperature is 120°C, an iron source is added and the reaction temperature is maintained to continue the reaction to obtain a product, and after washing and drying, the single-atom iron-anchored covalent triazine framework Fe-CTFs is obtained, wherein the iron element accounts for 0.5%-4% of the mass of the single-atom iron-anchored covalent triazine framework Fe-CTFs; the iron source is a soluble salt of divalent or trivalent iron, and its anion is selected from at least one of chloride ion, nitrate ion and sulfate ion.
2. The method according to claim 1, characterized in that The molar ratio of the 1,4-terephthalaldehyde to terephthalamidine hydrochloride is 1:(1.5-2.5).
3. The method according to claim 1, characterized in that The alkaline catalyst is cesium carbonate.
4. The method according to claim 1, characterized in that: The solvent is a mixed solvent of dimethyl sulfoxide and water.
5. The method according to claim 1, characterized in that The gradient temperature increase is specifically: heating the reaction at 60°C for 12-14h, then heating the reaction at 80°C for 12-14h, then heating the reaction at 100°C for 12-14h, and finally heating the reaction to 120°C.
6. The method according to claim 5, characterized in that The reaction time after adding the iron source is 72-76h.
7. The method according to claim 1, characterized in that The iron source is ferrous sulfate.
8. The method according to claim 1, characterized in that The iron element accounts for 2% of the mass of the single-atom iron-anchored covalent triazine framework Fe-CTFs.
9. A single-atom iron-anchored covalent triazine framework, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Use of the single-atom iron-anchored covalent triazine framework as claimed in claim 9 in photocatalytic degradation of pollutants.